David Frazer (Foster, Vic. : David Foster, 2006)
This the website of artist David Frazer
Title from title page (viewed on 9 June 2009)
Text and images.
Mode of access: Internet via World Wide Web. Available at: http://www.dfrazer.com
Selected for archiving
Keywords: Art, Australian; Artists -- 20th century; Painting -- 20th century; Sculpture -- Australia; Wood-engraving -- 20th century